Biokeys – an integrated system for working with database and polyclave identification keys of various taxonomic levels - Sinh, Nguyen Van (Vietnam Journal of Science and Technology, 2015)
Unlike the other currently available identification software, BioKeys allows the users to create and use own polyclave identification keys of various taxonomic levels. The information of dedicated taxonomic level is stored in the head line of the key file so that BioKeys can understand and search in the right field of the database for the records of matched taxa. The results of database referencing or specimen identification will be displayed in a form of web page. Besides, utilities are available for creating and managing the database, for analyzing the polyclave identification key. An example of using BioKeys is provided with polyclave key of plant families of Magnoliophyta that has been created based on the punched-card system of Bertel Hansen and Knud Rahn (1969).